Inequality of learning in industrialised countries - John Micklewright; Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2006)
Within-country differences in educational outcomes are compared for a large group of industrialised countries. We investigate where inequality is greatest, the association between inequality in learning and average levels of learning, the interpretation of measured levels of inequality, and differences in inequality at the top and bottom of the national distributions. Our analysis is based on test score data for 21 countries present in the Trends in International Mathematics and Science Study (TIMSS), the Programme for International Student Assessment (PISA), and the Progress in International Reading Literacy Study (PIRLS). The use of three different surveys avoids reliance on a single source.
urn:nbn:de:101:1-20080502133
Keywords: 330